Typical Bengkulu Rafflesia Flower Pattern in Waistbag Design - christy aryani, willia; Indra Gunara Rochyat (TEXTURE Art and Culture Journal, 2025)
The purpose of this research is to describe the process of making the Rafflesia Arnoldii flower pattern decoration and to find out the finished results of applying the Rafflesia Arnoldii flower pattern decoration on the waistbag and highlighting the characteristics of Bengkulu. The theme of the creation of this work of art is the Rafflesia Arnoldii flower pattern because it has a visually stunning shape that makes it unique from other flowers. It has an attraction, most people like this flower because of its shape, size and unique way of life. Lives in the tropical rainforests of Sumatra; Therefore, Bengkulu Province is nicknamed "Land of Rafflesia Arnoldii". It is a symbol of Bengkulu Province because it is very rare and must be protected. The method used is a three-stage design process, one of the stages is creative exploration. From the results obtained, the Rafflesia Arnoldii flower pattern can be used as a detail for the waistbag design. The aesthetic value of this waist bag design is not only for a sporty and masculine style appearance, but also for a feminine and elegant appearance with the addition of the Rafflesia Arnoldii flower pattern so that it becomes a waist bag design with aesthetic value that can be enjoyed by everyone and becomes an innovative design product with exploratory design. The concept created by adding added value in the form of Bengkulu characteristics is expected to create new market opportunities for waistbag products.